Cough-relieving peach blossom powder as well as preparation method and quality detection method thereof
By using the "nuclear-shell" composite particle technology and high-efficiency liquid color spectrum detection method in cough peach blossoms, the uniformity and quality stability of the preparation of the differences in the differences of the variety of Chinese medicine compound raw material traits are solved, and the liquidity and the uniformity of ingredients are realized. Significant improvement.
Patent Information
- Application Number
- CN202411533729.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
AI Technical Summary
During the preparation process, due to the differences in the source and properties of the raw materials of the Chinese medicine compound, the particle size, density, color, etc. of each medicinal material after pulverization, affecting the uniformity and quality stability of the preparation. The existing quality testing methods can only detect a single raw material or heavy metal, and cannot effectively control product quality.
Adopt the "nuclear-shell" composite particle technology, use mint fine powder as a nuclear particles, and the French Pinellia ultra-micro powder as the shell particles. The crushing time is rationally controlled through the ultra-micro crushing machine to prepare a composite particle with improving liquidity and uniformity. Based on the high -efficiency liquid chromatography method to detect the nucleoside substances in the prescription, ensure that the content of the ingredients is uniform.
It significantly improves the liquidity and the uniformity of ingredients, improves the quality stability of the preparation, and provides an efficient detection method suitable for determining the content of nucleoside.
Smart Images

Figure CN119367463A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to cough-relieving peach blossom powder and a preparation method and a quality detection method thereof, belonging to the field of medicines. Background Art
[0002] The prescription of Peach Blossom Powder for Relief of Cough was first seen in Zhang Zhongjing's Treatise on Febrile Diseases. It is used as an antitussive for whooping cough and chronic cough, and measles combined with pneumonia. Its prescription is composed of Fritillaria cirrhosa, Pinellia tuber, Gypsum, Cinnabar, Musk, Mint, and Borneol, and has the effects of clearing the lungs, resolving phlegm, relieving cough, opening the orifices and dispersing heat, and calming the nerves. It is used as an antitussive for whooping cough and chronic cough, and measles combined with pneumonia. Zhang Wei et al., Clinical Observation on the Treatment of Acute Tonsillitis in Children with Integrated Traditional Chinese and Western Medicine, Shanxi Traditional Chinese Medicine, Vol. 22, No. 4, August 2006, discloses that Peach Blossom Powder for Relief of Cough is used to treat acute tonsillitis in children.
[0003] During the preparation of cough-relieving peach blossom powder, due to differences in the sources and properties of the raw materials of the Chinese herbal compound, the particle size, density, color, etc. of each medicinal material after crushing are different, which has a great impact on the uniformity of the effective ingredients of the preparation, resulting in unstable quality of the preparation, which is not conducive to clinical application.
[0004] In addition, Zhike Taohua Powder is included in the "Drug Standards of the Ministry of Health·Chinese Patent Medicine Formula Preparations (Volume 12)". The original standard does not have a content determination item. There are literature reports that the redox titration method was used to detect cinnabar in the prescription (Wang Li, et al., Determination of the Content of Cinnabar in Zhike Taohua Powder, Vol. 22, No. 20, October 20, 2013), and there are also reports that the atomic absorption spectrophotometry was used to determine the mercury and arsenic content in Zhike Taohua Powder (Chen Demiao, Determination of the Content of Mercury and Arsenic in Zhike Taohua Powder by Atomic Absorption Spectrophotometry, Vol. 26, No. 1, January 5, 2017). The quality inspection methods currently reported are only for the detection of single raw materials or heavy metals, which cannot achieve the purpose of controlling product quality.
[0005] Chinese medicine powder is an important material basis for solid Chinese medicine preparations, and powder is the main form of powder, which is one of the oldest traditional dosage forms. There are a lot of records of powders in the ancient classic medical masterpieces "Treatise on Febrile Diseases", "Famous Doctors' Records" and "Shennong's Herbal Classic". In addition, Chinese medicine powder is also an intermediate for the preparation of other dosage forms, which is of great significance to the preparation and research and development of dosage forms. However, due to its complex physical and chemical properties, when powders with different properties are used to form Chinese medicine compounds, it often leads to pharmaceutical problems such as poor mixing uniformity. It will further affect the subsequent molding process, resulting in differences in the content of active ingredients in solid preparations, affecting clinical drug safety.
[0006] The characteristics of Chinese medicine powder affect the mixed molding of preparations. Under the guidance of the theoretical ideas of traditional Chinese medicine, combined with powder materials and the production and processing methods of Chinese medicine pieces, the introduction of Chinese medicine powder modification technology can solve the problems of poor fluidity and strong hygroscopicity of Chinese medicine powder preparations. Powder modification technology uses physical and chemical methods to change the state of the powder itself, and then change the physical and chemical properties, so as to improve the prescription function. Applying powder modification technology to solid preparations of traditional Chinese medicine and improving the pharmaceutical method from the perspective of powder science is of great significance for improving the efficacy of Chinese medicine prescriptions and the secondary application of Chinese medicine products, making traditional Chinese medicine preparations closer to modern preparations. Among them, particle coating technology is one of the common means of powder modification. Through equipment such as ball mills and ultrafine grinders, shell particles with smaller particle sizes are orderly embedded on the surface of core particles with larger particle sizes. This process should reasonably control the "shell-core" structure particle size ratio to achieve the purpose of modification. Thereby improving the overall powder characterization properties of the prescription, and at the same time, it can achieve the purpose of correcting bad odors and achieving ideal drug release speed. Chen et al. introduced magnesium stearate, a pharmaceutical excipient, and ultrafinely ground it with fine powders of dandelion and old dragon bark to prepare "core-shell" composite particles. They found that when the dosage of magnesium stearate was 2% and the composite time was 3 minutes, the prepared composite particles could significantly improve the poor fluidity of the powder raw materials and the uneven content of ingredients. For example, application number 202311692733.1, invention name: Xiaoer Baoan Powder and its preparation method, with powder particles of borneol, ginger pinellia, asarum, silkworm, coptis and cinnabar as core particles, and powder particles of bitter almond frost, mint, gastrodia, Poria, patchouli, pearl, amber, malt, tangerine peel, platycodon, angelica and Liushenqu as shell particles, the purpose is to solve the oral compliance of the drug and solve the irritating odor and micro-toxicity of the core particles themselves. Therefore, based on different purposes, the way of powder modification is also different. Summary of the invention
[0007] Preliminary studies of the present invention have found that the mint raw material of cough-relieving peach blossom powder has poor fluidity, which easily causes uneven content of ingredients in the overall prescription, and is one of the factors affecting the uniformity of cough-relieving peach blossom powder.
[0008] The technical solution of the invention is to provide a new cough-relieving peach blossom powder, and provide a preparation method and a quality detection method of the cough-relieving peach blossom powder.
[0009] The present invention provides a cough-relieving peach blossom powder, which is composed of the following raw materials in the following weight proportions:
[0010] 30 parts of Fritillaria cirrhosa, 9 parts of artificial musk, 6 parts of borneol, 9 parts of mint, 6 parts of water-blasted cinnabar, 12 parts of French pinellia, and 30 parts of calcined gypsum;
[0011] It is a "core-shell" composite particle prepared with ultrafine powder of Pinellia ternata as shell particles and fine powder of peppermint as core particles; it is then mixed with fine powder of Fritillaria cirrhosa, musk, borneol, ultrafine powder of cinnabar, and fine powder of calcined gypsum, ground, sieved, and mixed to obtain cough-relieving peach blossom powder.
[0012] The grinding time of the ultrafine powder of Pinellia ternata is 15-30 minutes; the "core-shell" composite particles are obtained by mixing the ultrafine powder of Pinellia ternata with the fine powder of peppermint, which are shell particles, evenly, and grinding them in an ultrafine grinder for 2-6 minutes.
[0013] Further preferably, the pulverization time of the ultrafine powder of Pinellia ternata is 20 minutes; the "core-shell" composite particles are prepared by mixing the ultrafine powder of Pinellia ternata with the core fine powder of Peppermint evenly, and pulverizing them in an ultrafine pulverizer for 4 minutes.
[0014] The present invention also provides a method for preparing the cough-relieving peach blossom powder, which comprises the following steps:
[0015] a. Weigh the APIs of various weight ratios;
[0016] b. Ultrafine grinding of French pinellia powder, grinding time 15-30min;
[0017] c. Mix the ultrafine powder of Pinellia ternata prepared in step b with the fine powder of Mentha arvense and put them into an ultrafine grinder for 2-6 minutes;
[0018] d. Mix the superfine powder of Pinellia ternata obtained by shell particle method and the fine powder of Peppermint obtained by core particle method evenly, and grind them in a superfine grinder for 2-6 minutes to obtain composite particles;
[0019] e. Grind cinnabar into extremely fine powder with water, crush Fritillaria cirrhosa and calcined gypsum into fine powder, add musk, borneol and the composite particles prepared in step d, grind, sieve and mix well to obtain cough-relieving peach blossom powder.
[0020] Among them, the pulverizing time described in step b is 20 minutes; the pulverizing time described in step d is 4 minutes; the conditions of the pulverizer used for ultrafine pulverization are: temperature -5°C, filling rate 80%, amplitude 5.5mm.
[0021] The invention adopts high performance liquid chromatography to detect nucleoside substances in cough-relieving peach blossom powder, and the chromatographic conditions are as follows: using an Agilent 5TC-C18(2)250×4.6mm, 5μm chromatographic column, the mobile phase is methanol (A): water (B), gradient elution 0-5min, A: 1%-2%; 5-15min, A: 2%; 15-20min, A: 2%-5%; 20-30min, A: 5%-15%; 30-35min, A: 15%; 35-40min, A: 15%-20%; 40-45min, A: 20%-1%; flow rate 0.8mL / min; detection wavelength 260nm; injection volume 20μL, column temperature 35℃; time 45min.
[0022] It includes the following steps:
[0023] a. Preparation of test solution
[0024] Weigh the sample, treat with ultrasound for 60 min, centrifuge at 10000 r / min for 10 min, filter through a 0.22 μm microporous membrane to obtain the test solution;
[0025] b. Preparation of reference solution
[0026] Weigh appropriate amounts of uracil, inosine, uridine, adenosine, guanosine, adenine, and thymidine reference substances, dissolve them in purified water, dilute to prepare a mixed reference substance solution of uracil (11.16 μg / mL), inosine (11.20 μg / mL), uridine (21.56 μg / mL), adenosine (13.54 μg / mL), guanosine (16.18 μg / mL), adenine (36.40 μg / mL), and thymidine (4.55 μg / mL), filter with a 0.22 μm microporous membrane, and take the filtrate to obtain the reference substance solution;
[0027] c. Preparation of negative sample solution
[0028] Remove the medicinal materials containing nucleoside components and prepare a negative sample solution according to the method of step a;
[0029] d. Detection by high performance liquid chromatography.
[0030] The present invention starts from the perspective of Chinese medicine powder modification, combines the concept of drug-excipient integration, and performs powder modification on the fine powder of the problematic herbal medicine that causes defects in prescription preparations, thereby solving the problems of cough-relieving peach blossom powder in mixing and uniformity. The present invention is the first to measure seven adenosine substances in cough-relieving peach blossom powder. The detection method has multiple advantages such as accuracy, sensitivity, high efficiency, and easy operation, and is very suitable for the content determination of nucleoside substances and the evaluation of prescription uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Time-particle size change pattern of prescription pieces (BH: mint; BP: borneol; SG: calcined gypsum; FBX: pinellia; CBM: fritillaria; ZS: cinnabar);
[0032] Figure 2 Comparison chart of bulk density of fine powder of medicinal pieces at seven sampling points;
[0033] Figure 3 Comparison chart of color difference values of seven sampling points of fine powder of medicinal pieces;
[0034] Figure 4 Ultrafine grinding time of shell particles / min;
[0035] Figure 5 Nuclear particle ultrafine grinding time / min;
[0036] Figure 6 Infrared spectra of each particle (A: mint; B: French pinellia; C: compounding for 2 min; D: compounding for 4 min; E: compounding for 6 min; F: physical mixing);
[0037] Figure 7 Microscopic morphology of particles of each sample (A: French pinellia; B: mint; C: compounding for 2 min; D: compounding for 4 min; E: compounding for 6 min; F: physical mixing);
[0038] Figure 8 Specificity investigation diagram (A, test solution; B: mixed reference solution; C: negative sample solution; 1-7: uracil, uridine, adenine, inosine, guanosine, thymidine, adenosine);
[0039] Fig. 9 Uniformity of nucleoside content;
[0040] Fig.10 SEM images of composite particle prescription stability (AD is the SEM scanning state of composite particles at zero frequency, low frequency, medium frequency, and high frequency intervention under a 1000x lens; EH is the particle state of composite particles at zero frequency, low frequency, medium frequency, and high frequency);
[0041] Fig.11 In vitro dissolution. DETAILED DESCRIPTION
[0042] Test Example 1 Preparation of cough-relieving peach blossom powder of the present invention
[0043] Except for musk and borneol, cinnabar is pulverized into very fine powder, and the rest of Fritillaria cirrhosa, Pinellia ternata, mint, and calcined gypsum are pulverized into fine powder. Pinellia ternata is ultrafinely pulverized for 20 minutes to prepare shell particles, and 12g of shell particles are taken for later use. Mint medicinal materials are pulverized into fine powder to obtain core particles, and 9g of core particles are taken. The shell and core particles are mixed evenly, put into an ultrafine pulverizer, and ultrafinely pulverized at -5℃ for 4 minutes to obtain composite particles.
[0044] Take 30g of Fritillaria cirrhosa powder, 9g of musk, 6g of borneol, 6g of cinnabar powder, 30g of calcined gypsum powder and 21g of the prepared composite particles, grind, sieve and mix well to obtain the composite prescription of cough-relieving peach blossom powder.
[0045] Test Example 2 Quality Testing Method of Cough-Relief Peach Blossom Powder of the Present Invention
[0046] 1. Uniformity of nucleoside content
[0047] In this prescription, Fritillaria cirrhosa, Pinellia ternata, and Mentha chinensis are all rich in nucleosides, which are basic substances for maintaining life activities and are also one of the key effective ingredients of commonly used animal medicines and Chinese medicines. The present invention intends to determine the content of nucleosides in the prescription to determine the uniformity of the prescription content. At the same time, Fritillaria cirrhosa, Pinellia ternata, and Mentha chinensis are all rich in nucleosides in this prescription, which are basic substances for maintaining life activities and are also one of the key effective ingredients of commonly used animal medicines and Chinese medicines. This method also provides a new reference method for nucleosides quality control, laying a foundation for subsequent determination of the content of nucleosides in prescriptions.
[0048] 2. Preparation of test solution
[0049] According to the sampling method of FDA's "Guidelines for Drug Sampling", 7 groups of samples were taken from the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder respectively, 3.0 g of the sample was accurately weighed, placed in a 50 mL conical flask, 30 mL of purified water was added, weighed, and ultrasonically treated for 60 min. After cooling, the lost mass was supplemented with purified water, shaken, and the solution was transferred to a centrifuge tube, centrifuged at 10000 r / min for 10 min, and then filtered with a 0.22 μm microporous filter membrane to obtain the test solution.
[0050] 3. Preparation of reference solution
[0051] Weigh appropriate amounts of uracil, inosine, uridine, adenosine, guanosine, adenine, and thymidine reference substances, dissolve them in purified water, dilute and prepare a mixed reference solution of uracil (11.16 μg / mL), inosine (11.20 μg / mL), uridine (21.56 μg / mL), adenosine (13.54 μg / mL), guanosine (16.18 μg / mL), adenine (36.40 μg / mL), and thymidine (4.55 μg / mL), filter through a 0.22 μm microporous filter membrane, and take the filtrate to obtain the reference solution.
[0052] 4. Preparation of negative sample solution
[0053] Remove the nucleoside-containing medicinal materials, accurately weigh 3.0 g, place in a 50 mL conical flask, add 30 mL of purified water, weigh, and ultrasonically treat for 60 min. After cooling, make up the lost mass with purified water, shake well, transfer the solution to a centrifuge tube, centrifuge at 10000 r / min for 10 min, filter, and filter with a 0.22 μm microporous filter membrane to obtain a negative sample solution.
[0054] 5. Chromatographic conditions
[0055] Agilent 5TC-C18(2)250×4.6mm,5μm chromatographic column was used, the mobile phase was methanol (A):water (B), gradient elution: 0-5min, A:1%-2%; 5-15min, A:2%; 15-20min, A:2%-5%; 20-30min, A:5%-15%; 30-35min, A:15%; 35-40min, A:15%-20%; 40-45min, A:20%-1%; flow rate: 0.8mL / min; detection wavelength: 260nm; injection volume: 20μL; column temperature: 35°C; time: 45min.
[0056] Test Example 3 Investigation of Steps and Parameters in the Preparation Method of the Cough-relieving Peach Blossom Powder of the Present Invention
[0057] 1. Investigation of the powder properties of single-ingredient medicines in the prescription of cough-relieving peach blossom powder and extraction of formulation defects
[0058] Sample preparation
[0059] Musk in this prescription is a precious medicinal material, and it requires more drugs to be crushed. Musk is not easy to be crushed, so the remaining six medicinal pieces are inspected. Six medicinal pieces such as Fritillaria cirrhosa are placed in a high-speed grinder. After crushing, the coarse powder of the medicinal pieces can pass through the No. 3 sieve. 200g of the coarse powder of the medicinal pieces is placed in an ultra-fine grinder for micronization (the temperature of the grinding chamber is -5°C, the fine powder grinding filling rate is 75%, and the crushing is 60min). Samples are taken at intervals, dried and stored for later use; at the same time, the fine powder of the six medicinal pieces is prepared (all pass through the No. 5 sieve, and contain no less than 95% of the powder that can pass through the No. 6 sieve).
[0060] 1.2 Particle size investigation
[0061] The above-mentioned decoction pieces powders were taken and the particle size of each sample was measured by the dry method of Microtrac laser particle size analyzer (S3500), and the different particle size distribution characteristic values (d10, d50, d90) of each sample were recorded. The regression equation between d90 (Y) and crushing time (X) was further established to explore the crushing law of drug decoction pieces. The results are shown below Figure 1 , Table 1.
[0062] Table 1 Prescription herbal medicine pieces crushing time (t)-particle size (d90) fitting equation
[0063]
[0064] According to the above chart analysis, the particle sizes of mint, Pinellia ternata, Fritillaria cirrhosa, and cinnabar show a "decrease-balance-increase" trend, and the correlation coefficients between the particle sizes of each medicinal piece and the crushing time are all greater than 0.9, proving that the ultrafine crushing time is closely related to the change in particle size. Mint, Pinellia ternata, Fritillaria cirrhosa, and cinnabar reached the minimum particle sizes of 55.235, 36.552, 41.058, and 40.045 μm at 23.10, 20, 13.504, and 9.305 minutes, respectively. Borneol and calcined gypsum showed an "increase-balance-decrease" trend, which is mainly attributed to the increase in the surface free energy of the medicinal piece particles under high-speed collision and shearing. In order to further ensure the overall stability, the particles will agglomerate with each other to further reduce the surface free energy, thereby increasing the particle size of the medicinal piece. In summary, the particle size is closely related to the crushing time.
[0065] 1.3 Determination of fluidity and wettability
[0066] Use BT-100 powder property tester to measure the angle of repose of each sample to further judge the fluidity of the powder. Place different samples on the sieve, turn on the instrument to let the sample fall slowly until the sample presents the highest cone, and use a protractor close to the cone to measure the angle of repose of the sample. Use K100C fully automatic surface tension and contact angle tester to measure the contact angle of each sample. Further judge the wettability of the powder. Take 0.2g of the sample to be tested, use a multifunctional tablet press to prepare the sample into a round tablet with a diameter of about 10mm and a hardness greater than 60N, and use pure water as the contact medium to measure the contact angle of each sample.
[0067] The angle of repose and contact angle of powder are important indicators for judging the fluidity and wettability of powder. The smaller the angle of repose and contact angle, the better the fluidity and wettability of powder, which also indirectly affects the preparation and stability of subsequent preparations. According to the comparison data of the angle of repose and contact angle in Table 2, the angles of repose of mint and borneol are large, and the fluidity of powder is poor, which indirectly affects the overall formulation evaluation (angle of repose>45°). In addition, the contact angles of the powders of each decoction piece in the prescription are large and the wettability is poor, which leads to defects in the entire formulation.
[0068] Table 2 Results of repose angle and contact angle measurement of cough-relieving peach blossom powder mixture and each decoction piece fine powder ( n=3)
[0069]
[0070]
[0071] 1.4 Determination of bulk density of fine powder of single herbal medicine pieces
[0072] The bulk density of each herbal medicine fine powder was investigated and measured by fixed volume. The herbal medicine samples of each unit were sampled with reference to the FDA's "Guidelines for Drug Sampling". The samples were slowly dropped from a fixed funnel so that the samples formed the highest cone at the bottom of the funnel. Samples were taken from the front (front powder), back (back powder), right side (right powder), left side (left powder), top (upper powder), center (middle powder), and bottom (lower powder) of the cone; a total of 7 sampling points. The sample was slowly dropped into a 1.5mL EP tube through a fixed funnel until the EP tube was filled, and the excess sample was scraped off. The bulk density of each sample was calculated by the mass and volume ratio. Each point was sampled three times, and the bulk density of the sample was measured in parallel.
[0073] From Table 3, the average bulk density values of the seven sampling points of the six-flavor decoction pieces of fine powder, including mint, borneol, calcined gypsum, French pinellia, Fritillaria cirrhosa, and cinnabar, are as follows. The RSD values of the bulk density of the seven sampling points of the single-flavor decoction pieces of fine powder are further calculated to be 7.48%, 5.23%, 0.61%, 0.74%, 0.59%, and 0.21%. The comparison results of the bulk density of the seven sampling points of the six-flavor decoction pieces of fine powder are shown in Figure 2 .
[0074] Table 3 Determination results of bulk density of fine powder of decoction pieces ( n=3)
[0075]
[0076] 1.5 Determination of the difference in fine pink color of single herbal medicine pieces
[0077] The difference in the fine powder color of the medicinal pieces was determined by a spectrophotometer. Sampling was performed according to the above-mentioned FDA sampling method, and fine powders from seven different sites of the six medicinal pieces were taken for testing. Seven groups of samples of fine powder of each medicinal piece were placed in the sampler of the spectrophotometer. After calibrating the instrument, the sample pool was installed and the measurement began. The CIE1976 color space was selected, and the difference in fine powder color was judged by calculating the comprehensive chromaticity value ΔE*ab=[(ΔL*)2+(Δa*)2+(Δb*)2]1 / 2. Each group was measured in parallel 3 times, and the comprehensive color difference value ΔE*ab was calculated.
[0078] 1.5.1 Precision test
[0079] According to the above method, the six-flavor decoction pieces of Zhike Taohua Powder were taken in turn, and the samples were measured continuously for 6 times according to the above method. The ΔE*ab comprehensive value was recorded, and the RSD was calculated to be less than 3%. The specific values are shown in Table 4. The results show that the instrument has good precision.
[0080] 1.5.2 Repeatability test
[0081] According to the above method, the six-flavor decoction pieces of Zhike Taohua Powder were taken in turn, and a total of seven samples of fine powder from different places were taken. The samples were measured according to the above method, the ΔE*ab comprehensive value was recorded, and the RSD was calculated to be less than 3%. The specific values are shown in Table 4. The results show that the method has good repeatability.
[0082] 1.5.3 Stability test
[0083] According to the above method, the six-flavor powder samples of Zhike Taohuasan were taken in turn, and the samples were measured at 0, 2, 4, 6, 8, 10, and 12 h respectively according to the above method, and the ΔE*ab comprehensive value was recorded. The RSD was calculated to be less than 3%. The specific values are shown in Table 4. The results show that the instrument has good stability.
[0084] Table 4 Methodological results of fine pink difference of decoction pieces
[0085]
[0086] The color difference values ΔE*dE*<comprehensive color difference value> of the fine powder of the six-flavor decoction pieces of Peach Blossom Powder for Cough Relief were measured three times at seven sampling points and are shown in Table 5.
[0087] Table 5 The difference results of fine pink color of six-flavor decoction pieces of cough-relieving peach blossom powder ( n=3)
[0088]
[0089] It can be seen from Table 5 that the average color difference values of the seven sampling points of the six herbal medicine powders, including mint, borneol, calcined gypsum, pinellia, Fritillaria cirrhosa, and cinnabar, are 58.223, 104.628, 101.916, 103.456, 101.917, and 85.688 respectively; the RSD values of the color difference values of the seven sampling points of the single herbal medicine powder are 4.012%, 1.214%, 0.005%, 0.011%, 0.125%, and 0.009%. The comparison results of the color difference values of the seven sampling points of the herbal medicine powder are shown in Table 5. Figure 3 .
[0090] By examining the bulk density and color difference value of the unit herbal medicine fine powder, the uniformity of the powder is measured according to the RSD value of the bulk density and color difference value. When the RSD of the bulk density and color difference value is large, it proves that the uniformity of the fine powder after crushing is poor and the mixing degree is low. According to the above experiments, it was found that the uniformity of mint and borneol fine powders was poor and the mixing degree was low. Combined with the characterization results of the angle of repose and contact angle, it was shown that the two may cause uneven mixing of the cough peach blossom powder powder and lead to poor drug uniformity. In order to further determine the key factors affecting the drug uniformity of cough peach blossom powder, the single herbal medicine fine powder with poor fluidity was removed, the angle of repose of the mixed powder was measured, and the main influencing factors were determined.
[0091] 1.6 Excluding some prescription fluidity studies
[0092] According to the above experiments, it was found that the angle of repose of mint, borneol, and calcined gypsum was large, and the powder fluidity was poor, which may lead to poor mixing of the prescription drugs. Therefore, the fine powders of mint, borneol, and calcined gypsum were removed in turn, and the angle of repose of the remaining drug mixtures was measured to determine the drug fluidity. See Table 6.
[0093] Table 6 Eliminate the angle of repose of the three medicinal pieces powder prescription ( n=3)
[0094]
[0095] Note: *P<0.05, **P<0.01 compared with the mint removal group.
[0096] The results showed that mint powder is a key factor affecting the drug uniformity of Zhike Taohua Powder, and is an important reason for poor prescription fluidity, which in turn leads to uneven preparation uniformity. In order to further improve the powder fluidity and drug mixing uniformity, the French Pinellia ternata with excellent fluidity and small particle size was subsequently selected as the shell particles. Through the mechanical particle composite method, the "core-shell" coated composite particles with French Pinellia ternata as the shell particles and mint decoction powder as the core particles were prepared, in order to improve the overall prescription fluidity and thus improve the preparation uniformity of Zhike Taohua Powder.
[0097] 2. Powder modified composite particles
[0098] 2.1 Investigation of shell particle size
[0099] The fine powder of Pinellia ternata was used as the initial material and put into the ultrafine grinder (temperature -5℃, filling rate 80%, amplitude 5.5mm) for intermittent sampling. The particle size of the powder was measured at different time periods to investigate the change law between the particle size of the powder and the grinding time. The change law of the grinding time of the shell particles is as follows: Figure 4 As shown. Where d90 is the particle size, the smaller the d90, the smaller the particle size. Figure 4 It can be seen that with the extension of ultrafine grinding time, the particle size of Pinellia ternata gradually decreases. Based on the particle size of d10 and d50, the ultrafine grinding time of shell particle Pinellia ternata is determined to be 20min.
[0100] 2.2 Investigation of core particle size
[0101] Mint powder was used as the initial material and put into the ultrafine grinder (temperature -5℃, filling rate 80%, amplitude 5.5mm) for intermittent sampling. The powder particle size at different time periods was measured to investigate the change law between the powder particle size and the grinding time. The change law of the core particle grinding time is as follows: Figure 5 As shown in the figure, as the crushing process progresses, the particle size of the mint gradually decreases. Based on the comparison of the particle sizes of d10 and d50, the mint fine powder can be directly identified as the core particles.
[0102] 2.3 Investigation of the powder properties of composite particles
[0103] Forming of "shell-core" composite particles: The shell particle method Pinellia ternata that was to be ultrafinely ground for 20 minutes and the core particle mint powder that was not ultrafinely ground were mixed evenly according to the prescription ratio (4:3), and then put into the ultrafine grinder and ultrafinely ground at -5°C to obtain the obtained particles. The shell particles and core particle powders were compounded in the ultrafine grinder to prepare composite particles of 2, 4, and 6 minutes, and their powder indicators were characterized.
[0104] The results of material particle fluidity and wettability at different ultrafine grinding times are shown in the table below. The fluidity of the modified composite particle material fine powder is improved compared with the original two-flavor herbal medicine mixed fine powder. The material shows the best fluidity and wettability when ultrafine grinding for 4 minutes. It can be preliminarily considered that the ultrafine grinding for 4 minutes is the best preparation process. IR, SEM and other technologies are subsequently introduced to examine the physical properties of the composite particles and observe the microstructure of the material.
[0105] Table 7 Results of investigation on the powder properties of composite particles ( n=3)
[0106]
[0107] Note: *P<0.05, **P<0.01 compared with the composite particle 4 min group.
[0108] 2.4 Investigation of physical properties of composite particles
[0109] 2.4.1 Infrared measurement
[0110] Take an appropriate amount of KBr and place it in a drying oven for 4 hours. Then take the sample to be tested and the dried KBr in a ratio of 1:100 into an agate mortar, grind and mix them well, press them into tablets, and measure the infrared spectrum of the sample. The obtained IR spectrum is shown in Figure 6 . French Pinellia is between 3000 and 2500 cm -1 There is one characteristic peak at 1500-500cm -1 There are three characteristic peaks. Among the composite particles ultrafinely crushed for 2, 4, and 6 minutes, only the composite particles ultrafinely crushed for 4 minutes show the same characteristic peaks at these wavelengths with higher peak intensities, indicating that the composite particles ultrafinely crushed for 4 minutes have better coating.
[0111] 2.4.2 Microstructure
[0112] A small amount of sample particles to be tested was placed on the sample holder and gold plated for 20 seconds at a working current of 10 mA and a working voltage of 4 mV. The morphological characteristics of each sample particle were observed under a scanning electron microscope. Figure 7 .
[0113] The shape of the particles of the French Banxia slices is mostly spherical, and the particles of the mint slices are irregular flaky structures. The microscopic characteristics of the particles of the French Banxia and mint slices can be clearly observed in the electron microscope image of the physical mixture, and no new structure is found, indicating that the two slices of the slices that exist simultaneously in the physical mixture only have a simple mixing relationship; the composite particles in Figures B, C, and D show a completely different microscopic morphology from the physical mixture. The composite particles are mostly in the form of agglomerates with rough surfaces and tight structures. The composite 4min particles can be observed to have spherical particles coated on the periphery of the irregular flaky structure, forming a kind of agglomerate particles with rough surfaces and tight structures. The composite 2min particles are larger and the coating structure is less tight, and the composite 6min particles are partially coated. This shows that the particle design technology has changed the microstructure of the mint slices, and the prepared composite particles have formed a new microstructure. Based on the results of infrared measurement and scanning electron microscopy observation of the microstructure, it is determined that the composite particles crushed for 4min have a better "core-shell" coating model.
[0114] 3. Evaluation of the original prescription of "shell-core" particle return cough-relieving peach blossom powder
[0115] 3.1 Sample preparation
[0116] Except for musk and borneol, cinnabar is pulverized into very fine powder, and the rest of Fritillaria cirrhosa, Pinellia ternata, mint, and calcined gypsum are pulverized into fine powder. Pinellia ternata is ultrafinely pulverized for 20 minutes to prepare shell particles, and 12g of shell particles are taken for later use. Mint medicinal materials are pulverized into fine powder to obtain core particles, and 9g of core particles are taken. The shell and core particles are mixed evenly, put into an ultrafine pulverizer, and ultrafinely pulverized at -5℃ for 4 minutes to obtain composite particles.
[0117] Take 30g of Fritillaria cirrhosa powder, 9g of musk, 6g of borneol, 6g of cinnabar powder, 30g of calcined gypsum powder and 21g of the prepared composite particles, grind, sieve and mix well to obtain the composite prescription of cough-relieving peach blossom powder.
[0118] Take 30g of Fritillaria cirrhosa powder, 9g of musk, 6g of borneol, 6g of cinnabar powder, 30g of calcined gypsum powder, 9g of mint powder, and 12g of Pinellia ternata powder, grind them, sieve them, and mix them well to get the original prescription of Peach Blossom Powder for cough relief.
[0119] 3.2 Particle size determination
[0120] The particle sizes of the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder were measured, as shown in Table 8. After adding the ultrafinely crushed composite particles, the particle size of the composite particle prescription decreased significantly.
[0121] Table 8 Particle size distribution comparison ( n=3)
[0122]
[0123] Note: Compared with the original prescription group of Zhike Taohua Powder, *P<0.05, **P<0.01.
[0124] 3.3 Determination of fluidity and wettability
[0125] The repose angle and contact angle of the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder were measured, as shown in Table 9. The fluidity and wettability of the compound prescription of Zhike Taohua Powder were improved to a certain extent, and the compound prescription of Zhike Taohua Powder could improve the shortcomings of the original prescription.
[0126] Table 9 Comparison of repose angle and contact angle distribution ( n=3)
[0127]
[0128]
[0129] Note: Compared with the original prescription group of Zhike Taohua Powder, *P<0.05, **P<0.01.
[0130] 3.4 Investigation of bulk density and color difference uniformity
[0131] Refer to the FDA "Guidelines for Drug Sampling" for sampling. Fix the funnel above the center of the white paper marked with a cross; slowly add sample particles to form a cone; take samples from the front (front powder), back (back powder), right (right powder), left (left powder), top (upper powder), center (middle powder), and bottom (lower powder) of the cone; a total of 7 sampling points.
[0132] The original prescription of cough-relieving peach blossom powder and the compound prescription of cough-relieving peach blossom powder were sampled according to the above method, and the bulk density of 7 samples was measured respectively, as shown in Table 10. The bulk density of the compound prescription of cough-relieving peach blossom powder increased, which may be due to the smaller particle size of the compound prescription of cough-relieving peach blossom powder, and it was found that the density fluctuation of the samples at the 7 sampling points of the compound prescription of cough-relieving peach blossom powder was small (RSD = 0.66%), indicating that the mixing uniformity between the particles of cough-relieving peach blossom powder was significantly improved. The color difference value ΔE*ab can be used to examine the mixing uniformity of the two samples. The greater the fluctuation of the color difference value of the sample, the worse the mixing uniformity. The color difference value of the samples at the 7 sampling points of the compound prescription of cough-relieving peach blossom powder fluctuated slightly (RSD = 0.13%), which once again proved that the mixing uniformity between the particles of the compound prescription was better. The comprehensive bulk density and color difference value measurement results (Table 11) showed that the uniformity of the compound prescription of cough-relieving peach blossom powder was significantly improved.
[0133] Table 10 Bulk density measurement results ( n=7)
[0134]
[0135] Table 11 Color difference value measurement results ( n=7)
[0136]
[0137] 3.5 Uniformity of Nucleoside Content
[0138] In this prescription, Fritillaria cirrhosa, Pinellia ternata, and Mentha arvense are all rich in nucleosides, which are basic substances for maintaining life activities and are also one of the key active ingredients of commonly used animal medicines. The present invention intends to determine the content of nucleosides in the prescription to determine the uniformity of the prescription content.
[0139] 3.5.1 Preparation of test solution
[0140] According to the sampling method of FDA's "Guidelines for Drug Sampling", 7 groups of samples were taken from the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder respectively, 3.0 g of the sample was accurately weighed, placed in a 50 mL conical flask, 30 mL of purified water was added, weighed, and ultrasonically treated for 60 min. After cooling, the lost mass was supplemented with purified water, shaken, and the solution was transferred to a centrifuge tube, centrifuged at 10000 r / min for 10 min, and then filtered with a 0.22 μm microporous filter membrane to obtain the test solution.
[0141] 3.5.2 Preparation of reference solution
[0142] Weigh appropriate amounts of uracil, inosine, uridine, adenosine, guanosine, adenine, and thymidine reference substances, dissolve them in purified water, dilute and prepare a mixed reference solution of uracil (11.16 μg / mL), inosine (11.20 μg / mL), uridine (21.56 μg / mL), adenosine (13.54 μg / mL), guanosine (16.18 μg / mL), adenine (36.40 μg / mL), and thymidine (4.55 μg / mL), filter through a 0.22 μm microporous filter membrane, and take the filtrate to obtain the reference solution.
[0143] 3.5.3 Preparation of negative sample solution
[0144] Remove the nucleoside-containing medicinal materials, accurately weigh 3.0 g, place in a 50 mL conical flask, add 30 mL of purified water, weigh, and ultrasonically treat for 60 min. After cooling, make up the lost mass with purified water, shake well, transfer the solution to a centrifuge tube, centrifuge at 10000 r / min for 10 min, filter, and filter with a 0.22 μm microporous filter membrane to obtain a negative sample solution.
[0145] 3.5.4 Chromatographic conditions
[0146] Agilent 5TC-C18(2)250×4.6mm,5μm chromatographic column was used, the mobile phase was methanol (A):water (B), gradient elution: 0-5min, A:1%-2%; 5-15min, A:2%; 15-20min, A:2%-5%; 20-30min, A:5%-15%; 30-35min, A:15%; 35-40min, A:15%-20%; 40-45min, A:20%-1%; flow rate: 0.8mL / min; detection wavelength: 260nm; injection volume: 20μL; column temperature: 35°C; time: 45min.
[0147] 3.5.5 Specificity inspection
[0148] Take the test sample, mixed reference solution, and negative sample solution respectively, and inject them according to the above chromatographic conditions. The results are shown below. Figure 8 , the negative solution has no interference.
[0149] 3.5.6 Drawing of standard curve
[0150] Take the reference solution under "3.5.2", accurately pipette different volumes of reference solution respectively, determine the content according to the chromatographic conditions under "3.5.3", draw the standard curve with the content of each reference solution (μg) as the horizontal axis and the peak area as the vertical axis, and get the regression equation. The results show good linear relationships.
[0151] Table 12 Linear investigation of seven chemical components
[0152]
[0153]
[0154] 3.5.7 Investigation of precision, repeatability, stability and sample recovery
[0155] Accurately aspirate 10 μL of the reference mixed solution, repeat the injection 6 times under the above chromatographic conditions, record the peak area, and calculate the peak area RSD <3%, indicating good precision. Take the same batch of samples of Zhike Taohua Powder, divide it into 6 parts of equal mass, prepare the sample solution according to the preparation method of the test solution, measure its peak area according to the required verification method, and calculate the peak area RSD <3%, indicating good repeatability. Take the Tianzhike Taohua Powder sample, prepare the test solution according to the test preparation method, measure the peak area by chromatography at 0, 2, 4, 6, 8, 10, 12, and 24h, and calculate the peak area RSD <3%, indicating that the sample has good stability at room temperature. Take six portions of the same batch of samples with known content, each portion is about 1.5g, accurately weighed, placed in a stoppered conical flask, accurately add appropriate amount of each reference solution to each portion, accurately add purified water to 30mL, prepare samples according to the test sample method, and determine according to the above method. The calculated recoveries are between 95% and 105%, indicating that the method is accurate and stable.
[0156] 3.5.8 Investigation of sample content uniformity
[0157] According to the sampling method in 3.5.1, 7 groups of samples were taken from the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder respectively, and the content of each sample was determined.
[0158] The results of the test are shown in Fig. 9The contents of effective chemical components in the 7 groups of samples of the original prescription of Zhike Taohua Powder were quite different, and the RSDs of uracil, uridine, adenine, inosine, guanosine, thymidine and adenosine were 20.59%, 21.30%, 22.12%, 22.10%, 20.12%, 24.96% and 14.18% respectively; the contents of effective chemical components in the compound prescription of Zhike Taohua Powder were relatively close, and the RSDs of uracil, uridine, adenine, inosine, guanosine, thymidine and adenosine were 5.14%, 4.13%, 6.18%, 13.32%, 5.12%, 8.38% and 9.82% respectively. It was found that the content of the original prescription was relatively low, which may be attributed to the uneven mixing of the original prescription powder, which further led to the low content of each measured component.
[0159] 3.6 Uniformity of cinnabar content
[0160] According to the sampling method of the FDA "Guidelines for Drug Sampling", 7 groups of samples were taken from the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder for determination of cinnabar content. About 1.0g of each sample particle was accurately weighed and placed in a Kjeldahl flask, and 20mL of sulfuric acid and 3g of potassium nitrate were added for heating and digestion. 3g of potassium nitrate was added every 30 minutes until the solution was nearly colorless, and then heating was stopped. The solution was cooled to room temperature, and then transferred to a conical flask. The flask was washed with 50mL of distilled water several times, and the washing liquid was added to the conical flask. 1% potassium permanganate solution was added dropwise until pink appeared, and 2% ferrous sulfate solution was added dropwise until the red color disappeared. 2mL of ammonium ferric sulfate indicator solution was added, and the solution was titrated with ammonium thiocyanate titrant until the solution was orange-red. The volume of titrant consumed was recorded. Each 1mL of ammonium thiocyanate titrant (0.1mol / L) was equivalent to 11.63mg of mercuric sulfide (HgS).
[0161] Table 13 Investigation on the uniformity of cinnabar content in two prescriptions
[0162]
[0163] Note: Compared with the original prescription group of Zhike Taohua Powder, *P<0.05, **P<0.01.
[0164] The content uniformity of HgS in the two sample particles was evaluated by titration. The results are shown in Table 13. The RSD value of the physical mixture reached 5.394%, the content distribution was discrete, and the uniformity was poor. The content difference and RSD value of the composite particles were both small, at 1.115% respectively. The content distribution was less discrete and the uniformity was better than that of the physical mixture.
[0165] 3.7 Structural stability evaluation
[0166] In order to evaluate the structural stability of the "shell-core" coated composite particles, the present invention simulates the collision and vibration that the preparation may be subjected to during transportation. 2The square area was used as the experimental area, and then divided into 4×4 small squares after being pasted with conductive tape. An appropriate amount of the sample to be tested was evenly blown onto the conductive tape experimental area, and the slide was fixed with transparent tape. The constant temperature oscillator was used to perform low frequency (50 Hz), medium frequency (100 Hz), and high frequency (300 Hz) interventions for 60 min in sequence, and the microscopic morphological changes were observed under a scanning electron microscope, such as Fig.10 shown.
[0167] After low-frequency intervention, the surface microscopic morphology of the composite particles did not change significantly, while the vibrations generated during the transportation of preparations in daily life are usually low-frequency oscillations, that is, the "shell-core" coating structure of the composite particles meets the stability requirements in daily environments. When the intervention frequency is increased, it is found that some fine particles fall off the surface of the composite particles, indicating that the "shell-core" coating structure between the composite particles is a soft coating that relies on the molecular forces between the particles, and its material basis has not changed.
[0168] 3.8 In vitro dissolution
[0169] Refer to "General Rule 0931" of Part IV of the 2020 edition of the "Chinese Pharmacopoeia" and use the paddle method to determine the dissolution rate. Accurately weigh 10g of the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder respectively, and weigh 3 parallel groups for standby. The dissolution medium of the dissolution apparatus is 900mL of 0.1mol / L hydrochloric acid, the working temperature is 37.5℃, the rotation speed is 100r / min, and the dissolution method is the paddle method. Samples are taken at 5, 10, 20, 30, 60, 90, 120, 150, 180, 210, and 240min, 4mL each time, and fresh dissolution medium of the same temperature and volume is supplemented at the same time; the sample is filtered through a 0.22um microporous filter membrane, and 20μL is injected for determination, and its solubility is calculated, see Fig.11 .
[0170] As the dissolution time increases, the dissolution behaviors of the seven ingredients in the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder are basically the same, with rapid dissolution from 0 to 30 minutes, followed by a plateau period, and a small increase in dissolution near the end of the dissolution time. The dissolution behaviors of the original prescription of Zhike Taohua Powder and the compound prescription of Zhike Taohua Powder are basically the same, and the composite particles basically do not change the dissolution of the drug.
[0171] The present invention is based on the idea of "quality comes from design", draws on particle design technology, combines the powder characteristics of cough-relieving peach blossom powder itself, and changes the microstructure and macroscopic properties of cough-relieving peach blossom powder materials through mechanical compounding process means without adding foreign substances. To a certain extent, it improves the pharmaceutical defects of cough-relieving peach blossom powder compound, such as poor taste, unstable properties, poor uniformity, etc., and preliminarily explores the feasibility of applying particle design technology in solid preparations of traditional Chinese medicine, providing reference value for the upgrading of traditional Chinese medicine solid preparation products and technical reform. At the same time, it provides new ideas and methods for the optimization of dosage forms of traditional Chinese medicine preparations rich in volatile oils and extremely unstable properties.
Claims
1. A cough-relieving peach blossom powder, characterized in that: It is composed of the following raw materials in weight ratio: 30 parts of Fritillaria cirrhosa, 9 parts of artificial musk, 6 parts of borneol, 9 parts of mint, 6 parts of water-blasted cinnabar, 12 parts of French pinellia, and 30 parts of calcined gypsum; It is a "core-shell" composite particle prepared with ultrafine powder of Pinellia ternata as shell particles and fine powder of peppermint as core particles; it is then mixed with fine powder of Fritillaria cirrhosa, musk, borneol, ultrafine powder of cinnabar, and fine powder of calcined gypsum, ground, sieved, and mixed to obtain cough-relieving peach blossom powder.
2. The cough-relieving peach blossom powder according to claim 1, characterized in that: The grinding time of the superfine powder of Pinellia ternata is 15-30 minutes; the "core-shell" composite particles are obtained by mixing the superfine powder of Pinellia ternata with the fine powder of peppermint, which are shell particles, evenly, and grinding them in a superfine grinder for 2-6 minutes.
3. The cough-relieving peach blossom powder according to claim 2, characterized in that: The grinding time of the ultrafine powder of Pinellia ternata is 20 minutes; the "core-shell" composite particles are prepared by mixing the ultrafine powder of Pinellia ternata with the fine powder of peppermint, and grinding them in an ultrafine grinder for 4 minutes.
4. The method for preparing the cough-relieving peach blossom powder according to any one of claims 1 to 4, characterized in that: It includes the following steps: a. Weigh the APIs of various weight ratios; b. Ultrafine grinding of French pinellia powder, grinding time 15-30min; c. Mix the ultrafine powder of Pinellia ternata prepared in step b with the fine powder of Mentha arvense and put them into an ultrafine grinder for 2-6 minutes; d. Mix the superfine powder of Pinellia ternata obtained by shell particle method and the fine powder of Peppermint obtained by core particle method evenly, and grind them in a superfine grinder for 2-6 minutes to obtain composite particles; e. Grind cinnabar into extremely fine powder with water, crush Fritillaria cirrhosa and calcined gypsum into fine powder, add musk, borneol and the composite particles prepared in step d, grind, sieve and mix well to obtain cough-relieving peach blossom powder.
5. The method for preparing the cough-relieving peach blossom powder according to claim 4, characterized in that: The pulverizing time in step b is 20 min; the pulverizing time in step d is 4 min; the conditions of the pulverizer used for ultrafine pulverization are: temperature -5°C, filling rate 80%, amplitude 5.5 mm.
6. The quality detection method of cough-relieving peach blossom powder according to any one of claims 1 to 3, characterized in that: The invention adopts high performance liquid chromatography to detect nucleoside substances in cough-relieving peach blossom powder, and the chromatographic conditions are as follows: using an Agilent 5TC-C18(2)250×4.6mm, 5μm chromatographic column, the mobile phase is methanol (A): water (B), gradient elution 0-5min, A: 1%-2%; 5-15min, A: 2%; 15-20min, A: 2%-5%; 20-30min, A: 5%-15%; 30-35min, A: 15%; 35-40min, A: 15%-20%; 40-45min, A: 20%-1%; flow rate 0.8mL / min; detection wavelength 260nm; injection volume 20μL, column temperature 35℃; time 45min.
7. The quality detection method of cough-relieving peach blossom powder according to claim 6 is characterized in that: It includes the following steps: a. Preparation of test solution Weigh the sample, treat with ultrasound for 60 min, centrifuge at 10000 r / min for 10 min, filter through a 0.22 μm microporous membrane to obtain the test solution; b. Preparation of reference solution Weigh appropriate amounts of uracil, inosine, uridine, adenosine, guanosine, adenine, and thymidine reference substances, dissolve them in purified water, dilute to prepare a mixed reference substance solution of uracil (11.16 μg / mL), inosine (11.20 μg / mL), uridine (21.56 μg / mL), adenosine (13.54 μg / mL), guanosine (16.18 μg / mL), adenine (36.40 μg / mL), and thymidine (4.55 μg / mL), filter with a 0.22 μm microporous membrane, and take the filtrate to obtain the reference substance solution; c. Preparation of negative sample solution Remove the medicinal materials containing nucleoside components and prepare a negative sample solution according to the method in step a; d. Detection by high performance liquid chromatography.
Citation Information
Patent Citations
Children security powder and preparation method thereof
CN117899180A